Inhibition of IKK-β by epidioxysterols from the flowers of Calotropis gigantea (Niu jiao gua). Issue 1 (December 2016) - Parhira, Supawadee; Zhu, Guo-Yuan; Li, Ting; Liu, Liang; Bai, Li-Ping; Jiang, Zhi-Hong
Abstract Background Calotropis gigantea (Asclepiadaceae) (Niu jiao gua ) has been used as a poultice in Chinese medicine for treating inflammatory skin diseases, e.g., neurodermatitis. This study aims to isolate the epidioxysterols from the flowers ofC. gigantea, elucidate their structures and evaluate their possible inhibitory effects on the NF-κ B pathway. Methods The two epidioxysterols 9, 11-dehydroergosterol peroxide (1 ) and ergosterol peroxide (2 ) were isolated from the powdered flowers ofC. gigantea by ultrasonic-assisted extraction, followed by the purification of the crude extract by column chromatography (i.e., silica gel and MCI-gel CHP 20P open columns). The chemical structures of these compounds were identified through a comparison of their HRMS, 1 H and13 C NMR data with those in the literature. The in vitro IKK-β inhibitory activities of compounds1 and2 (1–100 µM) were evaluated using an IKKα andβ Assay/Inhibitor Screening Kit, which is a single-site, semi-quantitative immunoassay. Berberine was used as a positive control. The IKK-β inhibitory activities between compounds1 and2 were compared by a two-tailed Student'st test to summarize the structure activity relationship. Results Compounds1 and2 exhibited a dose-dependent inhibitory activity towards IKK-β in a similar manner to that of berberine. The IKK-β inhibitory activities of these two epidioxysterols were significantly stronger (P = 0.001 for compound1 andP = 0.028 for compound2 ) than that of berberine at the concentration of 100 µM. Furthermore, at the same concentration the suppressive effect of compound1 towards IKK-β was greater than that of compound2 (P = 0.041), while their activities at 10 and 50 µM were comparable. The difference in the results at 100 µM therefore suggested that the double bond between C-9 and C-11 in compound1 could be responsible for its higher inhibitory activity towards IKK-β at this concentration. Conclusions 9, 11-dehydroergosterol peroxide (1 ) and ergosterol peroxide (2 ) were isolated from the flowers ofC. gigantea and exhibited in vitro inhibitory activities towards IKK-β .